Learning To Live Together: Promoting Social Harmony - Kelso, J. A. Scott; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book is devoted to the issue of how we can learn to live together in the face of division and conflict. It is dedicated to the life and work of a remarkable human being, Dr Epimenidis Haidemenakis, scientist, statesman, visionary leader, President Emeritus of the International S.T.E.P.S. Foundation and founding father of The Olympiads of the Mind (OM). The monograph consists of a collection of papers presented at the 8th and 9th Olympiads of the Mind held in Washington, DC and Chania, Crete respectively. Distinguished international scholars, government and corporate representatives, leading researchers and academics from multiple disciplines and Nobel Laureates Leon Lederman (Physics, 1988), Martin Perl (Physics, 1995) and Yuan T. Lee (Chemistry, 1986) address a broad range of issues all with the aim of improving the human condition and achieving cooperation among the people of the world. The topics include the environment, sustainabilityand security; diversity and how to achieve integration and peace among people in a fractured world; the important role of brain research; how to overcome poverty and inequality; how to enhance creativity and improve education at all levels; and how new technologies and tools can be used for common benefit. The culmination of the book is a call to action, to join what one might call the "OM Movement"-bringing the best minds in the world together to create solutions to world issues so that we can all live together in harmony. .
The State Of The World -- Diversity And Integration -- The Brain's Trust -- Education And Culture -- Technology -- Messages And Recommendations.
Keywords: Quality of life; International relations; Dynamics; Nonlinear theories; Environmental economics; Environmental policy; Neurosciences; Quality of Life Research; International Relations; Applied Dynamical Systems; Environmental Economics; Environmental Policy; Neuroscience